The Influence of Service Quality, Price, and Brand Loyalty on Motorcycle Purchase Decision at Dealer CV. Andalas Motor Bengkalis - Malika Nefti Budi Asih; Hutomo Atman Maulana (Inovbiz: Jurnal Inovasi Bisnis Seri Manajemen, Investasi dan Kewirausahaan, 2021)
This study aims to determine the effect of Service Quality, Price, and Brand Loyalty on Motorcycle Purchase Decisions at dealer CV.Andalas Motor Bengkalis. This research is associative research. The population used by consumers who buy motorbikes at dealer CV Andalas Motor Bengkalis with a sample size of 100 respondents. The technique used is multiple linear regression with the regression model Y=1.821 + 0.163X1 + 0.299X2 + 0.207X3 + e. The results of this study indicate that partially service quality has a positive and significant effect on purchasing decisions with tcount 2.466, price has a positive and significant effect on purchasing decisions with tcount 4.045. Brand loyalty has a positive and significant effect on purchasing decisions with tcount 6.158. Simultaneously, Service Quality, Price, and Brand Loyalty have a positive and significant effect on motorcycle purchasing decisions at dealer CV.Andalas Motor Bengkalis with Fcount 67.837 seen from the coefficient of determination 67.9%.